The definition of double commutators and consistency in free field theory - Pawlowski, Jan M. (Arxiv, 1996)
Within the framework of generalized functions a general consistent definition of double commutators is given. This definition respects the Jacobi identity even if the regularization is removed. The double commutator of fermionic currents is calculated in this limit. We show that BJL--type prescriptions and point--splitting prescriptions for calculating double commutators fail to give correct results in free field theory.